2012
DOI: 10.1111/j.1755-0238.2012.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of berry ripeness on concentration, qualitative composition and extractability of grape seed tannins

Abstract: Background and Aims:The evolution of seed tannins in three grape varieties grown in the same vineyard was followed from preveraison to harvest, to determine their pattern of accumulation. Also, to elucidate whether the use of 70% acetone as extracting solvent overestimate what will occur during fermentation, seed tannins were extracted throughout the ripening period with a method that involved a 3 days extraction with aqueous 12.5% ethanol and the results compared with the acetone extraction method. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 28 publications
7
64
3
Order By: Relevance
“…The PAs compositions and TTC were determined by HPLC and a spectrophotometric method, respectively. In the skin and seeds, TTC was significantly decreased at grape berry maturity, which was consistent with previous studies (Gagne et al 2006;Bucchettia et al 2011;Lorrain et al 2011;Bautista-Ortín et al 2012). EBR treatment enhanced accumulation of PAs both in the skin and seeds (Supplementary Table 3), which was fully consistent with previous results for TTC in 'Cabernet Sauvignon' and 'Yan 73' grapes (Xi et al 2013b).…”
Section: Discussionsupporting
confidence: 93%
“…The PAs compositions and TTC were determined by HPLC and a spectrophotometric method, respectively. In the skin and seeds, TTC was significantly decreased at grape berry maturity, which was consistent with previous studies (Gagne et al 2006;Bucchettia et al 2011;Lorrain et al 2011;Bautista-Ortín et al 2012). EBR treatment enhanced accumulation of PAs both in the skin and seeds (Supplementary Table 3), which was fully consistent with previous results for TTC in 'Cabernet Sauvignon' and 'Yan 73' grapes (Xi et al 2013b).…”
Section: Discussionsupporting
confidence: 93%
“…Aqueous acetone (70% v/v), a common and high-yielding solvent for extraction of phenolic substances (Cheng et al 2012), was compared with a wine-like extraction medium containing 12.5% (v/v) ethanol (Bautista-Ortín et al 2012). Aqueous acetone (70% v/v), a common and high-yielding solvent for extraction of phenolic substances (Cheng et al 2012), was compared with a wine-like extraction medium containing 12.5% (v/v) ethanol (Bautista-Ortín et al 2012).…”
Section: Extraction Of Phenolic Substances From Grape Skin and Seedmentioning
confidence: 99%
“…Skins and seeds from 10 frozen berries were separately extracted in 15-mL glass vials containing 10 mL of 70% v/v acetone in water (Kallithraka et al 1995) or 10 mL of hydroalcoholic solution containing 12.5% (v/v) ethanol and 2 g/L potassium hydrogen tartrate (pH 3.6) (Bautista-Ortín et al 2012). Vials were sparged with nitrogen before being sealed and incubated at 23°C in the dark on an orbital shaker (200 rpm) for 24 or 72 h for the 12.5% ethanol or 70% acetone solutions, respectively.…”
Section: Extraction Of Phenolic Substances From Grape Skin and Seedmentioning
confidence: 99%
“…The qualitative and quantitative phenolic composition of grapes depends on multiple factors, including climate, variety, soil, water availability, and degree of ripeness (Bautista-Ortín et al, 2012). Several studies have shown that phenols in seeds accumulate before the onset of ripening or veraison, reaching a maximum around veraison and decreasing towards harvest (Ferrer-Gallego et al, 2010;Kennedy et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%